Glycemic control levels in diabetic patients through glycated hemoglobin in an urban area of ​​Villa El Salvador, Lima, Peru - Guevara-Tirado, Alberto (2022)
The most efficient glycemic control evaluation measure currently in diabetic patients is the determination of glycated hemoglobin (Hba1c) (desirable level <7 In Peru, diabetes is one of the most important public health problems due to the high burden The objective is to determine the levels of glycemic control in diabetic patients treated in a private medical center in an urban area of ​​Lima, Peru during the year 2020. with ages equal to or greater than 39 years with diagnosis and treatment of diabetes mellitus for 1 year or more Among the results we have that glycated hemoglobin in the studied population is 7.78% metabolic in these patients and it is necessary to rethink health measures at all levels of care.